2013
DOI: 10.1002/chem.201300477
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Metal–Organic Frameworks through the Postsynthetic Transformation of Olefin Side Groups

Abstract: For the first time, the adaptability of the C=C double bond as a versatile precursor for the postsynthetic modification (PSM) of microporous materials was extensively investigated and evaluated. Therefore, an olefin-tagged 4,4'-bipyridine linker was synthesized and successfully introduced as pillar linker within a 9,10-triptycenedicarboxylate (TDC) zinc paddle-wheel metal-organic framework (MOF) through microwave-assisted synthesis. Different reactions, predominately used in organic chemistry, were tested, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 54 publications
1
21
0
1
Order By: Relevance
“…Both bromination with elemental bromine and a UV‐initiated thiol‐ene click reaction using ethyl mercaptane proceeded in nearly quantitative yields and good conversions of the double bond, which were comparable to the results of our previous work . Although crystallinity was retained in both cases according to PXRD, the accessible BET surface area of the activated samples dropped to 5 and 52 m 2 g −1 , respectively.…”
Section: Resultssupporting
confidence: 86%
“…Both bromination with elemental bromine and a UV‐initiated thiol‐ene click reaction using ethyl mercaptane proceeded in nearly quantitative yields and good conversions of the double bond, which were comparable to the results of our previous work . Although crystallinity was retained in both cases according to PXRD, the accessible BET surface area of the activated samples dropped to 5 and 52 m 2 g −1 , respectively.…”
Section: Resultssupporting
confidence: 86%
“…Rieger et al [67] reported an olefinfunctional MOF, in which the adaptability of the C=C double bond for PSM was extensively investigated and evaluated. Until now, there are only two examples regarding to PSM of MOFs via thiol-ene reaction.…”
Section: Psm Of Mofs Through Thiol-ene Reactionmentioning
confidence: 99%
“…In principle, it can also be applied to covalently attach functional groups within the framework of MOFs. However, to our surprise, the thiol-ene reaction had only been utilized to chemically tailor the pore surface of an olefin-tagged Zn paddle-wheel MOF until recently [13]. In this manuscript, we reported the second example of the PSM of MOF through thiol-ene reaction.…”
Section: Introductionmentioning
confidence: 89%
“…1 H NMR (300 MHz, CDCl 3 , ppm): δ¼8.11 (d, J ¼7.9 Hz, 4H), 7.66 (d, J ¼7.9 Hz, 4H), 6.99 (s, 2H), 3.95 (s, 6H), 3.81 (s, 6H). 13 C NMR (75 MHz, CDCl 3 , ppm): δ¼167.0, 150.7, 142.8, 130.0, 129.43, 129.39, 128.8, 114.5, 56.4, 52 Synthesis of 5: A solution of compound 4 (253 mg, 0.72 mmol) in dry DMF (20 mL) was treated with potassium carbonate (540 mg, 3.9 mmol) and ally bromide (0.6 mL, 6.94 mmol) under N 2 . The resulting reaction mixture was heated at 80 1C for 60 h before H 2 O (50 mL) was added.…”
Section: Ligand Synthesismentioning
confidence: 97%